Testing of PLL-based True Random Number Generator in Changing Working Conditions - M. Simka; M. Drutarovsky; V. Fischer (Radioengineering, 2011)
Security of cryptographic systems depends significantly on security of secret keys. Unpredictability of the keys is achieved by their generation by True Random Number Generators (TRNGs). In the paper we analyze behavior of the Phase-Locked Loop (PLL) based TRNG in changing working environment. The frequency of signals synthesized by PLL may be naturally influenced by chip temperature. We show what impact the temperature has on the quality of generated random sequence of the PLL-based TRNG. Thank to analysis of internal signals of the generator we are able to prove dependencies between the PLL parameters, statistical parameters of the generated sequence and temperature. Considering the measured results of experiments we form a new requirement in order to improve the robustness of the designed TRNG.